O wielkiej dyferencjacji i konwergencji - Kwiecień, Michał (Człowiek i Społeczeństwo, 2016)
The book Great Divergence and Great Convergence: A Global Perspective is an attempt at analysis of historical process that led to current state of global socioeconomic system. Grinin and Korotayev suggest that both Great Divergence and Great Convergence are two different stages of the same process called by them Global Modernization. Authors also claim that globalization have weakened the core and strengthened the periphery of World System due to “law of communicating vessels” of global economy. The purpose of this paper is to reconstruct authors’ view on nature of historical process and to present non-Marxian historical materialism as an alternative theory.